Artificial Intelligence Systems - Melnyk, Halyna; Melnyk, Vasyl (My University, 2025)
This textbook provides theoretical foundations and methodological guidelines for laboratory and practical tasks in the course "Artificial Intelligence Systems." Recommended for students of the Faculty of Mathematics and Informatics.
Textbook
Keywords: AI; NLP; ML; Computer Vision; Genetic Algorithms